Pesquisa de Trichinella spiralis em roedores capturados na zona portuária de Santos - Paim, Gil Vianna; Côrtes, Valdson de Angelis [UNESP] (Universidade de São Paulo (USP), Faculdade de Saúde Pública, 1979)
Examinaram-se 594 diafragmas de roedores capturados na zona portuária de Santos tendo em vista a procura de larvas de Trichinella spiralis. Todos os diafragmas examinados estavam negativos.

Five hundred and ninety-four diaphragms of rodents captured in the Santos dock area were examined for Trichinella spiralis. The results of the examinations were negative.
An investigation of Trichinella spiralis in rodents captured in the Santos dock area
Keywords: Trichinella spiralis; Triquinelose; Zoonoses; Trichinella spiralis; Trichinosis; Zoonoses